Tìm x, biết: x^3 + 27 + (x + 3)(x - 9) = 0
Tìm x, biết: x3 + 27 + (x + 3)(x – 9) = 0.
Tìm x, biết: x3 + 27 + (x + 3)(x – 9) = 0.
x3 + 27 + (x + 3)(x – 9) = 0
\( \Leftrightarrow \)(x3 + 33) + (x + 3)(x – 9) = 0
\( \Leftrightarrow \)(x + 3)(x2 – 3x + 9) + (x + 3)(x – 9) = 0
\( \Leftrightarrow \)(x + 3)(x2 – 3x + 9 + x – 9) = 0
\( \Leftrightarrow \)(x + 3)(x2 – 2x) = 0
\( \Leftrightarrow \)(x + 3).x.(x – 2) = 0
\( \Leftrightarrow \left[ \begin{array}{l}x + 3 = 0\\x = 0\\x - 2 = 0\end{array} \right. \Leftrightarrow \left[ \begin{array}{l}x = - 3\\x = 0\\x = 2\end{array} \right.\).
Vậy phương trình đã cho có 3 nghiệm phân biệt là x = −3; x = 0; x = 2.